Market reactions to the appointment of audit committee directors with financial and industry expertise in Germany - Sascha Kieback; Martin Thomsen; Christoph Watrin (International Journal of Auditing, 2022)
Several calls from practitioners and the relevant literature suggest that audit committee directors with industry expertise complement the knowledge of financial experts. Thus, this study examines market reactions to the voluntary appointment of new audit committee directors with financial and industry expertise in Germany. Using hand-collected German data on newly appointed audit committee director announcements, we find a significantly positive market reaction around the appointment of financial experts with industry expertise but no reaction around the appointment of financial experts without industry expertise. Consistent with the expectation that some industries demand a higher need for specialised directors, we find a positive market reaction to the appointment of financial experts with industry expertise depending on whether the appointing firm is relatively more challenging for non-industry experts to monitor and advise. Overall, our findings suggest that market participants demand a combination of financial and industry expertise.
Keywords: 650; audit committee; boards of directors; corporate governance; financial expertise; industry expertise; market reaction